Maternal knowledge, attitude and practice regarding commercial oral rehydration salt solution: experience from a diarrhoeal disease hospital in Bangladesh - Tahmeed Ahmed; Mohammod Jobayer Chisti; Md Fuad Al Fidah; Sharika Nuzhat; Md Ridwan Islam; Shoeb Bin Islam; Md Mushfiqur Rahman; Sneha Paul; Mahfuz-Un Nesa; Devjani Chowdhury; Shayontan Fardin Nabi; Awni Mokhtar Sallam Ali Awn; et al. (BMJ Paediatrics Open)
Background Despite oral rehydration salt (ORS) solution being a life-saving medication, mothers of affected children often lack proper knowledge and exhibit improper practice of using ORS in sachets. We aimed to assess maternal knowledge, attitude and practice towards commercially available ORS and its use in treating under-5 children with diarrhoea.Methods The study was conducted at the Dhaka Hospital, Bangladesh. We included 350 mothers of under-5 children suffering from diarrhoea. Data were collected using a pretested questionnaire and modified Bloom’s cut-off was used to determine adequate knowledge (≥80%), positive attitude (≥90%) and proper practice (≥75%). Logistic regression models were developed after adjusting for confounding variables. Adjusted ORs (AORs) and their 95% CIs were reported.Results The prevalence of inadequate knowledge, negative attitude and improper practice was 88.0%, 59.1% and 72.5%, respectively. Participants with up to the higher secondary level of education had significantly higher odds of possessing adequate knowledge (AOR 7.47; 95% CI 2.76 to 20.12) and following proper practice (AOR 3.04; 95% CI 1.66 to 5.77). The majority (97.4%) reported being aware of the process of ORS preparation. Only 2.9% correctly knew all recommended steps. Approximately half (51.1%) knew the purpose of ORS use, and 24.6% believed that antibiotics are more helpful than ORS.Conclusions The findings of the study emphasise the need for substantial improvements to the existing health education program with a focus on parental education. Emphasis should be given to reading instruction on the sachet and promoting access to information via mass media outlets.